A new species of Sinonichnus Jałoszyński in China (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2025)
Sinonichnus Jałoszyński is an endemic Chinese genus currently including only two species: S. yunnanensis (Jałoszyński, 2019) and S. leiodicornutus Jałoszyński, 2021. Both species occur in Yunnan. Sinonichnus montanus sp. nov. is described, based on a male specimen collected close to the type localities of the previously known species.